KEGIATAN KAJIAN METODE HISAB AWAL BULAN QAMARIYAH - Asrul, Asrul; Nadhif, Nadhif (IAIN Ternate, 2024)
The study on determining the beginning of the Qamariyah month conducted online on Saturday, March 9, 2024, aimed to enhance participants' understanding of the principles of this and its application for determining the start of the Qamariyah month. This event featured two speakers who covered two main topics: the definition of hisab, the evidence for its legitimacy, understanding the texts, and the meanings of hadiths, as well as the role of hisab, types of hisab, criteria for hisab, the authentic method of hilal observation, and its implementation for the beginning of Ramadan 1445 Hijriyah in Yogyakarta and Ternate. The training results indicated that participants gained a profound knowledge of the hisab method and could apply this knowledge in their religious practices. The use of online technology via Zoom proved effective for organizing the training, and participant feedback indicated satisfaction with both the content and the delivery of the training. This training successfully achieved its educational goals by enhancing participants' competence in determining the beginning of the Qamariyah month in a syar'i and practical manner.ABSTRAKKegiatan Kajian metode hisab awal bulan Qamariyah yang dilaksanakan secara daring pada Sabtu, 9 Maret 2024, bertujuan untuk meningkatkan pemahaman peserta kajian tentang prinsip-prinsip hisab dan aplikasinya dalam penentuan awal bulan Qamariyah. Kegiatan ini menghadirkan dua narasumber yang membahas dua materi utama: pengertian hisab, dalil pensyariatan, fahmul matan, dan ma'anil hadits serta kedudukan hisab, macam-macam hisab, kriteria hisab, hisab hakiki wujudul hilal, dan implementasinya untuk awal Ramadhan 1445 Hijriyah di Yogyakarta dan Ternate. Hasil pelatihan menunjukkan bahwa peserta memperoleh pengetahuan yang mendalam tentang metode hisab dan dapat menerapkan ilmu tersebut dalam praktek ibadah. Teknologi daring melalui Zoom terbukti efektif dalam menyelenggarakan pelatihan, dan umpan balik dari peserta mengindikasikan kepuasan terhadap materi dan penyampaian yang dilakukan. Pelatihan ini berhasil memenuhi tujuan edukatifnya dengan meningkatkan kompetensi peserta dalam menentukan awal bulan Qamariyah secara syar'i dan praktis